2019
DOI: 10.1111/jcpe.13214
|View full text |Cite|
|
Sign up to set email alerts
|

Akkermansia muciniphila reduces Porphyromonas gingivalis‐induced inflammation and periodontal bone destruction

Abstract: Aim: Akkermansia muciniphila is a beneficial gut commensal, whose anti-inflammatory properties have recently been demonstrated. This study aimed to evaluate the effect of A. muciniphila on Porphyromonas gingivalis elicited inflammation. Material and Methods:In lean and obese mice, A. muciniphila was administered in P. gingivalis-induced calvarial abscess and in experimental periodontitis model (EIP).Bone destruction and inflammation were evaluated by histomorphometric analysis.In vitro, A. muciniphila was co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 39 publications
(57 reference statements)
2
77
0
Order By: Relevance
“…Other studies have also shown the anti-inflammatory properties of A. muciniphila in different mouse models including germfree, liver injury and obesity models (59-64). Huck et al (62) reported that A. muciniphila could reduce inflammation induced by Porphyromonas gingivalis in lean or obese mice. Ansaldoi et al (59) demonstrated that A. muciniphila plays a contextdependent role in the induction of gut-resident T-cells during homeostasis in mice.…”
Section: The Multifunctional Properties Of a Muciniphilamentioning
confidence: 99%
“…Other studies have also shown the anti-inflammatory properties of A. muciniphila in different mouse models including germfree, liver injury and obesity models (59-64). Huck et al (62) reported that A. muciniphila could reduce inflammation induced by Porphyromonas gingivalis in lean or obese mice. Ansaldoi et al (59) demonstrated that A. muciniphila plays a contextdependent role in the induction of gut-resident T-cells during homeostasis in mice.…”
Section: The Multifunctional Properties Of a Muciniphilamentioning
confidence: 99%
“…P. gingivalis which detected with greater frequency and at higher levels at periodontal sites is strongly associated with periodontal disease and has been considered as a major etiologic agent for periodontitis 22 , 23 . In the present study, we determined the effect of quercetin on gingipain activities, hemagglutination activity, hemolytic activity, biofilm formation, hydrophobicity and aggregation, which all contribute to P. gingivalis virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of reactive oxygen species (ROS) is considered to be a factor in which inflammation of the gingiva affected diabetic retinopathy [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Porphyromonas gingivalis ( P. gingivalis ) and Fusobacterium nucleatum ( F .…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis ( P. gingivalis ) and Fusobacterium nucleatum ( F . nucleatum ) are the major periodontal bacteria that cause gingival inflammation [ 26 , 27 ]. It has been reported that diabetic model rats infected with P .…”
Section: Discussionmentioning
confidence: 99%